Study of Fatigue Behaviour Of High Speed Steel Skh51 In Forging Process - Chan, King Sern (2020)
Forging has long been an interest in the metal forming industry due to its low production cost and ability of producing high strength product. It has a wide range of application in producing the product for automobiles, aerospace, machinery, hand tools and hardware, and even the fittings and valves. However, fatigue failure is the main issue of forging tools. Forging tools will fail from time to time due to the effect of cyclic loading that leads to fatigue failure. High speed steel (HSS) SKH51 is one of the popular forging tool steel used in forging industry. Hence, the fatigue behaviour of this tool steel is crucial and in depth study should be done. In considering of this, a series of methodologies have been planned and done to determine the mechanical properties and fatigue behaviour of HSS SKH51 in forging process. Mechanical properties will have a great effect on the fatigue behaviour of this tool steel. From the results obtained, it is proven that HSS SKH51 exhibits a variety of prominent mechanical properties and highly reliable fatigue behaviour. It has a high hardness of HRC 61.1, high ultimate engineering compressive stress of 5920.58 MPa, high critical load of 120 kN and endurance limit of 780 MPa in tensile fatigue test. Fatigue behaviour will in turn affect the fatigue life of a forging tool. There are many types of forging process available in the industry and clinching process is selected as the example in current project for predicting the tool life. The prediction shows that HSS SKH51 square clinching tool is having a higher number of cycles to failure (579 281 cycles) and thus, it is more recommended to be used in the industry instead of HSS SKH51 round clinching tool (63 834 cycles). In conclusion, it can be summed up that HSS SKH51 has a superb fatigue behaviour with long tool life and it could be beneficial when it is used as the forging tool steel. Future work can be done by modifying the validated simulation models to improve the fatigue behaviour of HSS SKH51 in forging process.